The antecedents of business owners’ intention to use cryptocurrency in emerging markets: The mediating role of attitude - Yamout, Racha; Saad, Rachel; Abass, Alaa Eldin; ElMoussaoui, Ali (Edelweiss Applied Science and Technology, 2025)
Cryptocurrency represents a breakthrough technology in the financial landscape, particularly in the way financial transactions and trading are conducted. This research explores the key drivers influencing individuals to adopt cryptocurrency for financial transactions in Lebanon, amid widespread distrust in the traditional banking sector. A quantitative research methodology was employed, utilizing Structural Equation Modeling and path analysis to evaluate the model and validate the hypotheses. Data was collected through a survey questionnaire sent to 400 respondents in Lebanon. The sample population includes CEOs, CFOs, entrepreneurs, and business owners who either use cryptocurrency or are willing to use it for financial transactions. The empirical findings reveal that facilitating factors such as ease of use and usefulness, along with attitude, are strong predictors of cryptocurrency adoption for financial transactions. This research offers both academic and practical insights by highlighting the importance of adopting a new currency for trading in emerging markets.